Therapeutic target exploration of Shugan Jianpi formula in liver fibrosis: an integrated lncRNA-mRNA co-expression network analysis - Kaiqiang Wan; Qiong Zhou; Ruirui Feng; Chang Fan; Weibing Shi; Wenbin Xu; Hui Jiang; Qiumei Zhou (Molecular Genetics and Genomics, 2026)

Evaluation and calculation of the 239Pu(n,f) cross section up to 200 MeV - Bo Gao; Changlin Lan; Bo Xie; Kuozhi Xu; Yanliang Chang; Muntazir Mehdi; Fanmin Zeng; Xiaonan Huang; Jianglong Pan; Ruirui Xu; Yue Zhang; Shilong Liu; et al. (Annals of Nuclear Energy, 2026)

Biosensor-driven adaptive laboratory evolution and modular pathway engineering for high-level production of nicotinamide mononucleotide in yeast - Ruirui Shi; Qiancheng Han; Yingxue Xu; Lei Li; Fuping Lu; Yixun Jiang; Zhengqiang Jiang; Hui-Min Qin (Bioresource Technology, 2026)

Temperature-dependent KMnO4 oxidative decrosslinking for enhanced permeance and scaling resistance of polyamide nanofiltration membranes - Ning Ma; Ruirui Jiang; Jielin Shi; Xinwei Kang; Jinyu Li; Feiyue Ge; Feilong Zhang; Feiyong Chen; Daliang Xu; Xuewu Zhu (Desalination, 2026)

Coupling heterovalent complementary doping with surface tailoring for stable O3-type layered oxide cathodes - Yang Liu; Haoji Wang; Yang Sun; Yingchang Yang; Wei Shi; Kaixu Yang; Jing Chen; Ruirui Wang; Xinyao Yang; Yanxu Wang; Haibiao Ning; Qifu Shi; et al. (Chemical Engineering Journal, 2026)

Super-resolution multimodal spatial transcriptomics reveals an ovoid stem cell niche structuring de novo shoot regeneration - Xiehai Song; Shaoman Zhang; Zhiliang Yue; Yongqi Liu; Shanshan Chen; Yani Niu; Yan Shi; Hengjia Yang; Jiahao Xu; Yuanyuan Miao; Meizhi Xu; Yingxue Zhou; et al. (Molecular Plant, 2026)

Sustainable lithium extraction from low-grade aqueous resources via reverse Li/Mg separation enabled by hydrated cation-π interaction - Huixiong Jiang; Xing Liu; Jin-Hang Liu; Xiudong Chen; Ruirui Wang; Yawei Wang; Changchao Zhan; Xiaohua Cao; Xiushen Ye; Guosheng Shi (Journal of Cleaner Production, 2026)

Transformation of microcrystalline and graphitization of particulate matter during DPF regeneration driven by non-thermal plasma: Mechanisms and reaction pathways - Yunxi Shi; Ruirui Ji; Yankang Huang; Xinyi Huang; Zhenguo Li; Jianbing Gao; Xiangyang Wang (Journal of Cleaner Production, 2026)

Degradation mechanism of diesel particulate emissions induced by non-thermal plasma - Yunxi Shi; Ruirui Ji; Xinyi Huang; Zhenguo Li; Jianbing Gao; Pan Wang; Jun Wang; Yixi Cai; Lei Yu (Journal of Environmental Chemical Engineering, 2025)

The role of silica in biomass for calcium-modified biochar: Phosphorus removal mechanism and potential as a phosphate fertilizer application - Yongyi Chen; Ruiling Zhang; Jiayong Gao; Mujun Han; Songyan Qin; Kai Liu; Yajie Shu; Ruirui Zhang; Chang Shi; Yue Zheng (Journal of Environmental Sciences, 2025)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

Hydrogen-rich water enhanced salt tolerance in tomato seedlings by regulating strigolactone biosynthesis genes SlMAX1 and SlD27 - Fujin Ye; Hua Fang; Li Feng; Meimei Shi; Ruirui Yang; Weibiao Liao (Plant and Soil, 2025)

Quercetin attenuates SiO2-induced ZBP-1-mediated PANoptosis in mouse neuronal cells via the ROS/TLR4/NF-κb pathway - Meichen Liu; Meichen Gao; Xu Shi; Yilin Yin; Huanyi Liu; Ruirui Xie; Chenxi Huang; Wenwen Zhang; Shiwen Xu (Journal of Environmental Management, 2024)

Mechanisms and characterization of interzone mass transfer inhomogeneity in PEM fuel cells - Huicui Chen; Enyang Shi; Ruirui Zhang; Peng Ren; He Wang; Zijing Zhu; Xi Fu; Pucheng Pei (Chemical Engineering Journal, 2024)

Construction of foam-like carbon microspheres with controllable pseudo-graphitic domains: Synergistic enhancement of K-ion adsorption/intercalation storage - Qingjuan Ren; Lei Yan; Xuewen Yu; Wenhua Lei; Zhongyu Sun; Ruirui Hao; Jianzeng Yang; Zhiqiang Shi (Chemical Engineering Journal, 2024)

Multidimensional combinatorial screening for high-level production of erythritol in Yarrowia lipolytica - Lei Li; Qianqian Zhang; Ruirui Shi; Mingdong Yao; Kangming Tian; Fuping Lu; Hui-Min Qin (Bioresource Technology, 2024)

Numerical simulation of CO2 storage by basalts in Xingouzui formation, Jianghan Basin, China - Ruirui Zhao; Zhi Zhong; Ying Yu; Rong Lü; Tingting Shi; Ningtao Wang; Jianmei Cheng (International Journal of Greenhouse Gas Control, 2024)

Mg Fe- layered double hydroxides (LDHs) modified electrode enhanced capacitive deionization for simultaneous phosphorus recovery and copper ions removal - Jingke Song; Chenyang Li; Xin Zhao; Ruirui Liu; Ruixue Han; Kai Jiang; Meiqing Shi; Dapeng Wu (Journal of Environmental Chemical Engineering, 2024)

Isolation methods, proliferation, and adipogenic differentiation of adipose-derived stem cells from different fat depots in bovines - Ruirui Zhu; Ye Feng; Ruirui Li; Kelong Wei; Yun Ma; Qingyou Liu; Deshun Shi; Jieping Huang (Molecular and Cellular Biochemistry, 2024)

The impact of agricultural productive service on agricultural carbon efficiency—From urbanization development heterogeneity - Rui Shi; Yujie Shen; Ruirui Du; Liuyang Yao; Minjuan Zhao (Science of The Total Environment, 2024)

The co-occurrent microplastics and nano-CuO showed antagonistic inhibitory effects on bacterial denitrification: Interaction of pollutants and regulations on functional genes - Ruirui Pang; Boqun Shao; Qiqing Chen; Huahong Shi; Bing Xie; Mostafa Soliman; Jun Tai; Yinglong Su (Science of The Total Environment, 2023)

Highly sensitive and quantitative fluorescent strip immunosensor based on an independent control system for rapid detection of tetrodotoxin in shellfish - Jiadi Sun; Zhixuan Shi; Ting Zhang; Liangzhe Wang; Ruirui Dong; Yinzhi Zhang; Xiulan Sun (Food Control, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Spatial–temporal dynamics of the built environment toward sustainability: A material stock and flow analysis in Chinese new and old urban areas - Dong Yang; Mengyuan Dang; Jing Guo; Lingwen Sun; Ruirui Zhang; Feng Han; Feng Shi; Qian Liu; Hiroki Tanikawa (Journal of Industrial Ecology, 2023)
The urban built environment has accumulated massive amounts of resources, which is the main “hot spot” of construction materials and energy consumption in cities. To effectively monitor and manage resources use and waste disposal toward sustainability, this study intended to explore different metabolic paths of the urban built environment, as well as strategies for new and old urban areas separately with the help of material stock and flow analysis. Based on snapshots of 2003, 2010, and 2017 and combined with big data, a four‐dimensional geographic information system buildings database of Lixia District in Jinan, China, was compiled for bottom‐up stock modeling. Finally, the environmental impact assessment of the buildings’ demolition and disposal stage was carried out. The results showed that the building material stock was 142.31 Mt in 2017, with an increase of 69% from 2003. The reinforced concrete buildings increased rapidly from 2003 to 2017, especially in new urban areas, which has boosted demand for steel and cement by more than 150% during these 15 years. The material stock of the old urban area tends to be saturated, whereas the new urban area has experienced a rapid expansion with the material inflow four times as large as the material outflow. Potential recycling of waste concrete can reduce the generation of building demolition waste by 50%, save 0.15 km 2 of land occupation, increase raw material substitution by nearly 10 times, and reduce CO 2 emissions by 2.5 times.

Farmers’ adoption behavior of conservation tillage technology: a multidimensional heterogeneity perspective - Yujie Shen; Wenting Kong; Rui Shi; Ruirui Du; Minjuan Zhao (Environmental Science and Pollution Research, 2022)

What matters most to the material intensity coefficient of buildings? Random forest‐based evidence from China - Ruirui Zhang; Jing Guo; Dong Yang; Hiroaki Shirakawa; Feng Shi; Hiroki Tanikawa (Journal of Industrial Ecology, 2022)
Material intensity coefficient (MIC) is vital for material stock accounting in the field of industrial ecology. However, the categorization of MIC varies across regions especially for buildings that diverge greatly along the history and space aspect, and acquisition of MIC data and building information have always been a challenge in related studies. In this study, the state‐of‐art ensemble model “Random Forest” was developed on Chinese buildings to identify the impact of four building attributes (building structure, construction year, use type, and region) on MIC, and these features’ importance was further assessed by considering variable correlations. The features’ importance and their individual effects on MIC were intuitively revealed by depicting the partial dependence plots. Finally, a set of hierarchical MIC values was estimated by integrating the order of four variables’ importance and a quick MIC calculator was provided. Results showed that building structure is the most influential attribute for MIC, followed by the construction year, use type, and region, successively. The RF‐based MIC values allow researchers to apply it to material stock and flow analysis by choosing a specific building feature(s) in the MIC calculator, which is (are) available in building physical inventory data. This study provides a method that could help researchers locate key influencing variables and give insights into the comparability of MIC research across regions and play an important role in developing urban mining and circular economy strategies.

The role of FATP1 in lipid accumulation: a review - Jieping Huang; Ruirui Zhu; Deshun Shi (Molecular and Cellular Biochemistry, 2021)

Overexpression of wheat α-mannosidase gene TaMP impairs salt tolerance in transgenic Brachypodium distachyon - Wenlong Wang; Yunzhen Wu; Ruirui Shi; Mengwei Sun; Qinxue Li; Guangqiang Zhang; Jiajie Wu; Yong Wang; Wei Wang (Plant Cell Reports, 2020)

Effects of Urban–rural Atmospheric Environment on Heavy Metal Accumulation and Resistance Characteristics of Pinus tabulaeformis in Northern China - Ruirui Zhao; Tong Yang; Cong Shi; Meili Zhou; Guoping Chen; Fuchen Shi (Bulletin of Environmental Contamination and Toxicology, 2019)

Toxicity bioassays for water from black-odor rivers in Wenzhou, China - He DeFu; Chen RuiRui; Zhu EnHui; Chen Na; Yang Bo; Shi HuaHong; Huang MinSheng (Environmental Science and Pollution Research, 2015)

Optical and SAR image registration based on improved nonsubsampled wavelet transform for sea islands - Wei Shi; Fenzhen Su; Ruirui Wang; Yongduo Lu (Acta Oceanologica Sinica, 2014)